Hubungan Status Ekonomi dengan Perilaku Perawatan Diri Pasien Diabetes Melitus Tipe 2 - Nur Wahyuni Munir (Lembaga Layanan Pendidikan Tinggi (LL-DIKTI) Wilayah IX Sulawesi, 2020)
Self-care behavior in diabetes mellitus patients consists of diet, exercise, drug therapy, foot care, and blood sugar monitoring. This study aims to determine the relationship between economic status and self-care behavior of type 2 diabetes mellitus patients at Puskesmas Tamamaung Makassar City. The research design used was an analytic survey with a cross sectional study approach. The sample determination was carried out by purposive sampling technique with a sample size of 41 respondents. The relationship test was performed using the Fisher Exact Test statistical test with a significance level of α <0.05. The results of this study indicate that there is no relationship between economic status and self-care behavior of type 2 diabetes mellitus patients at Puskesmas Tamamaung Makassar City (ρ = 0.219).